EVALUATION OF CYTOTOXIC ACTIVITY AND ANTHELMINTIC PROPERTY OF CHLOROFORM EXTRACT OF CLITORIA TERNATEA L. - KANTHAL, LAKSHMI KANTA; NAIDU, ADARI VENKATA RAJULU; LAKSHMI, PILLA NAGA; BABURAO, YADALA; BHAR, KAUSIK (International Journal of Current Pharmaceutical Research, 2016)
Objective: The objective of the present work was to evaluate the phytochemical study, cytotoxic activity and anthelmintic property of the whole plant chloroform extract of Clitoria ternatea L. Methods: The chloroform extract was tested for protein, amino acids. alkaloids, glycosides, flavonoids, tannins, steroids, saponins. The in vitro cytotoxic activity of chloroform extract was performed by MTT assay method against HepG2 (Liver carcinoma), HeLa (Cervix carcinoma) cell lines. 25, 50 and 100 mg/ml concentration of chloroform extract of Clitoria ternatea L. whole plant were taken for performing anthelmintic activity against adult Indian earthworm Pheritima posthuma. Results: The preliminary phytochemical tests revealed that chloroform extract of Clitoria ternatea L. contains amino acids, alkaloids, glycosides, flavonoids, tannins, saponins, steroids. Effect of inhibition of cell growth showed significant cytotoxicity against HepG2 with an IC50 of 110.00Â±1.9 Î¼g/ml and against HeLa with an IC50 of 104.50Â±0.9Î¼g/ml. The crude chloroform extract (25, 50, 150 mg/ml concentration) of Clitoria ternatea L. whole plant shows potent anthelmintic activity against Pheritima posthuma. Conclusion: The present study concluded that Clitoria ternatea L. can be considered as an important source of natural products that have anti-cancer potentials and potent anthelmintic activity.